2014
DOI: 10.1002/ajmg.c.31413
|View full text |Cite
|
Sign up to set email alerts
|

The transcriptional regulator ADNP links the BAF (SWI/SNF) complexes with autism

Abstract: Mutations in ADNP were recently identified as a frequent cause of syndromic autism, characterized by deficits in social communication and interaction and restricted, repetitive behavioral patterns. Based on its functional domains, ADNP is a presumed transcription factor. The gene interacts closely with the SWI/SNF complex by direct and experimentally verified binding of its C-terminus to three of its core components. A detailed and systematic clinical assessment of the symptoms observed in our patients allows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 51 publications
2
74
0
4
Order By: Relevance
“…Remarkably, ADNP is one of a relatively small group of genes that appear to lead to autism in a substantial proportion of cases. Immediately following our initial report, two additional patients were identified that share many of the reported characteristics (Pescosolido et al 2014;Vandeweyer et al 2014). On top of that, Coe et al (2014) reported five patients with a truncating ADNP mutation in a screening of 4716 patients with autism/ID.…”
mentioning
confidence: 97%
“…Remarkably, ADNP is one of a relatively small group of genes that appear to lead to autism in a substantial proportion of cases. Immediately following our initial report, two additional patients were identified that share many of the reported characteristics (Pescosolido et al 2014;Vandeweyer et al 2014). On top of that, Coe et al (2014) reported five patients with a truncating ADNP mutation in a screening of 4716 patients with autism/ID.…”
mentioning
confidence: 97%
“…Once recurrent genetic loci have been identified through genetic testing, individuals with ASD and an identified genetic event should be evaluated clinically in order to determine whether phenotypic characteristics suggest a unique ASD subtype (e.g., CHD8) . Previous associations have been found between genes associated with ASD and intellectual disability (Kaufman et al, 2010), and already specific gene disrupting mutations identified through molecular subtyping show co-morbidity with significant cognitive deficits (e.g., ADNP, PTEN) (Frazier et al, 2014;Helsmoortel et al, 2014;Vandeweyer et al, 2014).…”
Section: Clinical Datamentioning
confidence: 99%
“…Even in its early stages, molecular subtyping with multiple integrated data methods has been shown to be successful in ASD research Frazier et al, 2014;Vandeweyer et al, 2014). Using exome and targeted sequencing technology, recurrent de novo disruptive mutations, such as CHD8, ADNP, DYRK1A, and PTEN have been found in individuals with ASD (Iossifov et al, 2014;O'Roak et al, 2012aO'Roak et al, , 2012b.…”
Section: Emerging Molecular Subtypes In Autismmentioning
confidence: 99%
See 2 more Smart Citations